KANITA-USM AIMS TO ADVANCE MATERNITY PROTECTION ISSUES IN 5-DAY RESEARCH WORKSHOP - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
GEORGETOWN, PENANG, 27 July 2016 – The Centre for Research on Women and Gender (KANITA) Universiti Sains Malaysia (USM) hopes to advance the issues surrounding maternity protection, female workforce and worklife balance with a 5day workshop entitled “Advancing Maternity Protection in Malaysia: Meeting Social Welfare and Business Needs and Contributing to Economic Development”, held in collaboration with Middlesex University (MDX) London at Holiday Inn Resort, Batu Feringghi here.